Numerical Simulation of Natural Frequency on Shaft Using ANSYS Software - Yopi Zekrri Jenizah Putra; Delima Yanti Sari; Waskito Waskito; Zainal Abadi (Unversitas Negeri Padang, 2025)
This descriptive study aims to analyze the effect of shaft diameter on the natural frequency and maximum deformation of a rotating shaft system. The analysis was conducted through numerical simulation using ANSYS Workbench software. The shaft and two symmetrically positioned disks were modeled, and a modal analysis was performed using the Finite Element Method (FEM) to determine the system’s first ten vibration modes. Simulation results showed that the natural frequencies ranged from 80.495 Hz to 280.4 Hz, with a maximum deformation of 58.903 mm occurring in the 9th mode. The lower modes (modes 1–6) exhibited lower frequencies but higher deformation, while higher modes (modes 7–10) showed more complex vibration patterns with consistently significant deformation values. This indicates that higher frequency does not necessarily result in lower deformation, and the system may still experience critical vibration. These findings demonstrate that the shaft's geometric configuration, including diameter and mass distribution of the disks, significantly affects its dynamic behavior. The simulation provides deeper insight into the vibration characteristics of the critical speed shaft apparatus used in practical experiments and serves as a reference for validating theoretical approaches such as the Dunkerley and Rayleigh methods.